Pemanfaatan Pewarna Alami Kain Tenun Futus Sebagai Alternatif Pewarna Preparat Jaringan Tumbuhan - Yolanda Getrudis Naisumu; Emilia Juliyanti Bria; Welli Herlince Kasse (BIOEDUSCIENCE, 2022)
Background: Natural plant dyes can replace synthetic dyes to reduce the negative effects caused. This study aims to determine the types of color-producing plants, the process of using natural dyes as dyes for plant tissue preparations and the percentage of quality and feasibility of plant tissue preparations. Methods: experiments were carried out in the application of natural plant dyes on plant tissue preparations. Data analysis was carried out to calculate the percentage of quality and feasibility of the preparations. Results: there were eight plant species from four families namely Fabaceae, Zingiberaceae, Maliaceae, and Lamiaceae. The process of processing plant parts into natural dyes is by soaking, boiling, pounding, grated and applied to preparations of corn and spinach plants. The use of natural dyes on corn and spinach preparations with a percentage of preparation quality ranging from 33.33% - 75.00% and said to be poor to good, while the percentage of feasibility of preparations ranged from 67.08% - 87.50% and was said to be feasible to very suitable for use in the observation of plant cells and tissues. Conclusions: Natural dyes from futus fabrics can replace synthetic dyes in dyeing plant tissue preparations.